Digital Content Marketing in the Business-to-Business Context : A Case Study on Marketing Communications Agencies - Kauhaniemi, Krista (fi=Turun yliopisto|en=University of Turku|, 2018)
Marketing has changed because of digitalization. Marketing is moving towards digital channels and more companies are transitioning from “pushing” advertising messages to “pull” marketing, that attracts audience with the content that interests and benefits the audience. This kind of marketing is called content marketing or “inbound” marketing. This study focuses on how marketing communications agencies utilize digital content marketing and what are the best practices with the selected digital content marketing channels. In this study, those channels include blogs, Facebook, Twitter, and LinkedIn. The qualitative research method was utilized in order to examine the phenomenon of digital content marketing in-depth. The chosen data collecting method was semi-structured interviewing. A total of seven marketing communications agencies, who currently utilize digital content marketing, were selected as case companies and interviewed. All the case companies are from the marketing communications industry because that industry can be assumed to be well adapted to digital content marketing techniques. There is a research gap about digital content marketing in the B2B context, which increases the novelty value of this research. The study examines what is digital content marketing, why B2B companies use digital content marketing, and how should digital content marketing be conducted through blogs and social media. The informants perceived digital marketing to be a fundamental part of their all marketing. They conduct digital content marketing for the following reasons: to increase sales, to improve their brand image and to demonstrate their own skills. Concrete results of digital content marketing for the case companies include sales leads, new clients, better brand image, and that recruiting is easier. The most important success factors with blogs and social media are the following: 1) Audience-centric thinking. All content planning should start from figuring out which themes interests the target audience. Social media channel choices should be based on where the target audience can be reached. 2) Companies should not talk only about themselves. Instead, content is made about themes that interests the target audience. On social media channels, only a fragment of all shared content is about the company. Rather, most of the shared content is industry-specific content that helps the potential client.